An Investigation of the Knowledge and Preferences of Parents About Dental Preventive Practices - Kızılay, Fatma Nur; Ayhan Kızılcı, Esra; Mahyaddinova, Türkan; Gümüşboğa, Zekiye Şeyma (European Journal of Therapeutics, 2024)
Objective: Dental caries poses a significant health concern affecting, 60%-90% of children globally. While fluoride is widely utilized to prevent and eliminate dental caries, recent negative media coverage and concerns about irresponsible fluoride use have prompted a shift in parental perspectives. This study explores parental knowledge, preferences, and attitudes regarding preventive measures, with a focus on fluoride and potential natural or herbal alternatives. Methods: Our research was designed as a survey study. A survey form consisting of 11 questions was delivered to parents of children aged 6–14 years and presented to the Erciyes University Department of Pediatric Dentistry for examination or treatment were included in the study. A total of 300 parents participated in the study. Data was recorded as numbers and percentages. Results: Of the parents, 69% (207) reported that if they were offered natural herbal compounds instead of fluorinated varnish, they would prefer natural alternatives. A statistically significant relationship was found between the responses received from the parents about the effects of fluoride and the educational level of the parents (p<0.05). Only 4 (1.3%) university graduate parents stated that fluoride had harmful effects. We found that 80.95% of the fathers and 68.39% of the mothers stated that they would prefer natural or herbal alternatives for their children instead of fluorinated varnish, and this was a statistically significant result (p<0.05). Conclusion: Parents do not have sufficient knowledge and attitudes about preventive practices in oral dental health, and some parents still avoid the use of fluoride products. Therefore, there is a need to increase fluoride intake and its effects on children’s health by educating parents or informing dentists.